HUBUNGAN PELAKSANAAN SURGICAL SAFETY CHECKLIST DAN KEJADIAN INFEKSI POST OPERASI MAYOR - Widiyaningsih Widiyaningsih; Eni Kusyati; Amri Hidayat (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2017)
Background: wound postoperative infection (ILO) are infections caused by pathogenic microorganisms that contaminate the wound area during surgery or after surgery. The data from survey by World Health Organization (WHO) found that about ILO cuased infection as 5% - 34% of total nosocomial infections. The data from Centers for Disease Control and Prevention cited that annually there was 500,000 surgical site infections (SSI) and that caused 3% surgical mortality, prolonged length of stay in hospital, and increased medical costs. Objective: to know the correlation of Surgical Safety Checlist Implementation and post operative infection. Research method: the method was quantitative method with cohort analytic survey design. The population were all patients with major surgery at Public Hospital of Tugurejo Semarang periode December 2016 - January 2017 as many as 99 patients. Result:the result of this study were major surgery mostly have implementation of surgical safety checklist either 81 respondent (81,8%) and have no infection incidence were 84 responden (84,8%). There was no significant correlation between surgical safety checklist implementation and postoperative infection.